A 21 Years Old Woman, with Chest Pain and Cardiac Dextroposition Pulmonary Hypoplasia or Scimitar Syndrome? - MoinAzad Tehrani, M; Agin, Kh (International Journal of Medical Toxicology and Forensic Medicine, 2013)
Background: Physicians seldom encounter chest x-ray of adult patients diagnosed with dextrocardia. Case presentation: Here, we present the case of a 21-year-old woman who referred to the hospital with the clinical diagnosis of dextrocardia but, she has pulmonary hypoplasia and this rare disease in adults may be a component of scimitar syndrome and scimitar sign is not pathognomonic to define the syndrome. MR angiography was done, but finally the diagnosis was hypoplasia of right upper lobe and aplasia of middle lobe. Conclusion: As lung hypoplasia is rare in adults, some cases are misdiagnosed as dextrocardia on chest x-ray.